DISSOLUTION BEHAVIOR OF BRASS POLARIZED BY ALTERNATING CURRENT IN SODIUM PHOSPHATE AQUEOUS SOLUTION - R.N. Nurdillayeva; A.B. Bayeshov; L.A. Sunatullaeva; G.N. Zhylysbayeva (Academic Scientific Journal of Chemistry, 2019)
The electrochemical behavior of Cu-Zn alloy (brass) polarized with industrial - frequency alternating current has been studied for the first time in aqueous sodium phosphate solution. The effects of current density in brass (200-1200 A/m2 ) and titanium (20-120 kA/m2 ) electrodes, sodium phosphate solution concentration (0,5-2,0 M), alternating current (AC) frequency (30-180 Hz) and electrolysis duration (0,25-1,5 h) on the alloy dissolution current efficiency were considered. Intensive brass dissolution by forming copper (II) and zinc (II) ions during the electrolysis in alternating current mode was shown for the first time. In the case of direct current (DC) electrolysis, the current output value of alloy electrochemical dissolution was very low. As the current density of the alternating current polarized brass electrode was increased, the current output rate of the alloy dissolution increased initially and decreased to 400 A/m2 , where (400 A/m2 ) alternating current value comprised 80% in an optimal condition. When the titanium electrode current density was increased, the brass dissolution current efficiency showed a maximum value; the current output of Cu (ІІ) and Zn (ІІ) ions formation at current 60 кА/m2 density was 50% and 30%, respectively. As the electrolysis duration and the AC frequency are increased, the brass electrode current efficiency is reduced. On the basis of obtained results, the potential of copper and zinc phosphate synthesis was shown.